Research on Experimental Hypertension in Prague (1966-2009) - Kuneš, J; Zicha, J (Physiological research, 2024)
The study of ontogenetic aspects of water and electrolyte metabolism performed in the Institute of Physiology (Czechoslovak Academy of Sciences) led to the research on the increased susceptibility of immature rats to salt-dependent forms of hypertension since 1966. Hemodynamic studies in developing rats paved the way to the evaluation of hemodynamic mechanisms during the development of genetic hypertension in SHR. A particular attention was focused on altered renal function and kidney damage in both salt and genetic hypertension with a special respect to renin-angiotensin system. Renal damage associated with hypertension progression was in the center of interest of several research groups in Prague. The alterations in ion transport, cell calcium handling and membrane structure as well as their relationship to abnormal lipid metabolism were studied in a close cooperation with laboratories in Munich, Glasgow, Montreal and Paris. The role of NO and oxidative stress in various forms of hypertension was a subject of a joint research with our Slovak colleagues focused mainly on NO-deficient hypertension elicited by chronic L-NAME administration. Finally, we adopted a method enabling us to evaluate the balance of vasoconstrictor and vasodilator mechanisms in BP maintenance. Using this method we demonstrated sympathetic hyperactivity and relative NO deficiency in rats with either salt-dependent or genetic hypertension. At the end of the first decennium of this century we were ready to modify our traditional approach towards modern trends in the research of experimental hypertension. Keywords: Salt-dependent hypertension o Genetic hypertension o Body fluids o Hemodynamics o Ion transport o Cell membrane structure and function o Renal function o Renin-angiotensin systems.
Keywords: Blood Pressure; Disease Models, Animal; History, 21st Century; Hypertension; krysa rodu Rattus; modely nemocí na zvířatech; dějiny 20. století; hypertenze; Animals; lidé; krevní tlak; History, 20th Century; renin-angiotensin systém; Humans; dějiny 21. století; zvířata; Renin-Angiotensin System; Rats